Suppression of porcine polyspermy using mechanical vibrations during in vitro fertilization - Takehiro HIMAKI; Kohei SHINADA; Asumi YAEGASHI (The Journal of Reproduction and Development)
The efficiency of porcine in vitro fertilized (IVF) embryo production remains low. Polyspermy is considered a contributing factor to this result. In this study, we investigated the effects of mechanical vibrations during the co-culture of oocytes and spermatozoa on fertilization parameters and subsequent embryonic development. The rate of polyspermy decreased significantly in all vibration culture groups compared with the stationary culture (control) group (P < 0.05). Regarding subsequent embryonic development, the blastocyst formation rate was significantly improved in the middle-vibration culture group compared with the control group (P < 0.05). However, the high-vibration culture group had the lowest sperm penetration rate and did not show any improvement in monospermy rate and normal fertilization efficiency. In addition, their in vitro developmental status was the lowest. These results indicate that moderate mechanical vibrations during insemination effectively suppress polyspermy and improve porcine IVF embryo production efficiency.